Computergestützte Verfahren zur pragmatischen Beurteilung der Tragwiderstände von Brettschichtholz: Zusammenfassung exemplarischer Simulationsstudien - Frese, Matthias (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2016)
This book contains experiences and results of computer simulations in the field of research on glued laminated timber. Literature and references to the corresponding methodical approach are given to facilitate the access to the elementary basics. It also contains constructive explanations and critical annotations on modelling glued laminated timber for bending, tension and compression tests. Finally, the relevance of the simulation results for practical issues is discussed.